Effective elastic properties of periodic fibrous composites. Limit cases. Applications to porous and nonlinear materials - Bravo-Castillero, Julián; Guinovart-Díaz, Raul; Rodríguez-Ramos, Reinaldo; Sabina, Federico J.; Valdiviezo-Mijangos, Oscar C.; Sabina-de-Lis, Jose Claudio (Computer Assisted Methods in Engineering and Science, 2022)
The goal of this contribution is to provide, based on the asymptotic homogenization method, helpful exact formulae to compute the overall stiffnesses and engineering moduli of a transversely isotropic twophase fibre reinforced composite with isotropic constituents. Comparison of the exact solution with known bounds is shown. In certain cases a bound is very close to the exact solution over a large interval. The bound then could be used as a good approximation to the exact solution. The exact formulae explicitly display Avellaneda and Swart's microestructural parameters, which have a physical meaning, and provide formulae for them. Hill's universal relations follow from the formulae. Limiting cases of rigid and empty fibers are included. An application of these results to improve bounds for the effective energy density of nonlinear dielectric fibrous composites is shown. Another application is related to bone poroelasticity.